2021
DOI: 10.3390/toxics9030063
|View full text |Cite|
|
Sign up to set email alerts
|

In-Vitro and In-Silico Assessment of Per- and Polyfluoroalkyl Substances (PFAS) in Aqueous Film-Forming Foam (AFFF) Binding to Human Serum Albumin

Abstract: Drinking water contaminated by fluorosurfactant-based aqueous film-forming foams (AFFF) is a source of human exposure to poly- and perfluoroalkyl substances (PFAS). However, assessment of bioaccumulation potentials of diverse PFAS in commercial products such as AFFF have been insufficient and challenging, especially due to a lack of analytical standards. Here we explore the value of suspect screening, equilibrium dialysis, and molecular-docking simulations to identify potentially bioaccumulative PFAS. We expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…This has been a serious challenge for pre-PFAA research because humans are exposed to a wide range of pre-PFAAs, some with unknown structures or no available neat standards. To circumvent this issue, a handful of studies have used commercial products, such as AFFF formulations, to dose in vivo and in vitro , models and measure known and novel transformation products. Others have used environmental samples containing complex PFAS mixtures .…”
Section: Future Perspectives and Paths Forwardmentioning
confidence: 99%
“…This has been a serious challenge for pre-PFAA research because humans are exposed to a wide range of pre-PFAAs, some with unknown structures or no available neat standards. To circumvent this issue, a handful of studies have used commercial products, such as AFFF formulations, to dose in vivo and in vitro , models and measure known and novel transformation products. Others have used environmental samples containing complex PFAS mixtures .…”
Section: Future Perspectives and Paths Forwardmentioning
confidence: 99%
“…Indeed, there are reports of binding interactions between C8 PFAS and proteins, such as human serum albumin (HSA) and bovine serum albumin (BSA). [29][30][31][32][33] However, very little is known about the interactions of other proteins with these contaminants. Moreover, even serum albumins have not been evaluated for their ability to remove PFOA and PFOS from water samples, and their ability to bind to shorter chain PFAS (<C8) has not been explored.…”
Section: Water Impactmentioning
confidence: 99%
“…Serum albumins are known to bind to both PFOA and perfluorooctane sulfonic acid PFOS, enabling their prolonged circulation in humans and animals. 26,[29][30][31][32][33][34][35][36][37][38][39] Chen et al observed that PFOA binds preferably to sub-domain IIA in BSA, while PFOS binds preferably to sub-domain IIIA. 38 Also, PFAS accumulates and distributes differently across several species, 2,[40][41][42][43] while ionic strength and pH can modulate PFAS binding to these proteins, too.…”
Section: Protein and Analyte Candidatesmentioning
confidence: 99%
“…The authors wish to make the following corrections to this paper [1]: There was an error in the original publication. In Section 4.2, the article stated, "HSA binding affinities of perfluorohexanesulfonic acid (PFHxS) and perfluoroheptanoic acid (PFHpA) were exceptionally high (Log K A : 5.89 ± 0.55 and 5.74 ± 0.38, respectively)".…”
Section: Text Correctionmentioning
confidence: 99%